Evaluation of training programs by medical employees in a chosen hospital in Poland - Anna Dudek-Kajewska; Beata Detyna; Jerzy Detyna (Managerial Economics)
Commitment in the professional role is undoubtedly a factor that influences professional success. A person who is well-equipped to perform their organizing role accepts the aims and duties set by the employees, acknowledges social norms of performance, and has the ability of satisfactory discharge of the duties, in aspect of their aims as well as the team’s aims (the team it cooperates with).Monitoring the degree of involvement and satisfaction with the tasks performed in the hospital should be one of the manager’s tasks. The systematic assessment of work quality, according to the authors, can become a source of knowledge about the employee’s needs. This, in turn, gives a chance to adjust motivational stimulus. One of them is purposeful training offer, accepted by the employees. It has a great importance in medical care facilities, where the health and lives of patients depend on the knowledge and skills of medical workers.